Strategies For Healthcare Workers Retention In Saudi Arabia: A Narrative Review Through The Lens Of Push-Pull Theory (Journal of Namibian Studies : History Politics Culture, 2022)
The healthcare systems are challenged to develop adaptable measures in place to meet the ever-increasing patients’ populations and needs. One of the adjustments that need a continuous and universal consideration is healthcare workers’ retention strategies. Yet, Saudi Arabia is one of the countries with high cases of health workers’ turnover. This narrative review explored the evidence-based healthcare workers’ retention strategies applicable in the situation of Saudi Arabia. Accordingly, four principal measures were noted, including adjustments on the policy frameworks, adjusting leaderships styles, modifying work environment, and improving compensations and rewards. These strategies need the attention of healthcare systems’ policymakers for effective implementation; however, with a sound consideration of the prevailing economic terms.